Navigation Made Personal: Inferring Driving Preferences from GPS Traces - Delling, Daniel; Goldberg, Andrew V.; Goldszmidt, Moises; Krumm, John; Talwar, Kunal; Werneck, Renato F. (23rd ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems. SIGSPATIAL '15 November 03 - 06, 2015, Bellevue, WA, USA, 2015)
All current navigation systems return efficient source-to destination routes assuming a -size-fits-all" set of objectives, without addressing most personal preferences. Although they allow some customization (likehighways" or tolls"), the choices are very limited and require some sophistication on the part of the user. In this paper we present, implement, and test a framework that generates personalized driving directions by automatically analyzing users' GPS traces. Our approach learns cost functions using coordinate descent, leveraging a state-of-the-art route planning engine for efficiency. In an extensive experimental study, we show that this framework infers user-specific driving preferences, significantly improving the route quality. Our approach can handle continental-sized inputs (with tens of millions of vertices and arcs) and is efficient enough to be run on an autonomous device (such as a car navigation system) preserving user privacy.